2019
DOI: 10.1029/2019jc015355
|View full text |Cite
|
Sign up to set email alerts
|

Southern Ocean Phytoplankton Blooms Observed by Biogeochemical Floats

Abstract: The spring bloom in the Southern Ocean is the rapid-growth phase of the seasonal cycle in phytoplankton. Many previous studies have characterized the spring bloom using chlorophyll estimates from satellite ocean color observations. Assumptions regarding the chlorophyll-to-carbon ratio within phytoplankton and vertical structure of biogeochemical variables lead to uncertainty in satellite-based estimates of phytoplankton carbon biomass. Here, we revisit the characterizations of the bloom using optical backscatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 97 publications
2
27
0
Order By: Relevance
“…These findings are broadly in agreement with those presented by Uchida et al (2019), who analysed the same dataset and found that early growth initiated in August/September in the region south of ∼60°S. However, the authors do not explicitly investigate growth in relation to the release of melt waters in the SSIZ, and appear to conclude that melting generally initiates growth through the release of iron trapped in sea ice, as well as the relief of light limitation.…”
Section: Relationship Between Melting and Growthsupporting
confidence: 89%
“…These findings are broadly in agreement with those presented by Uchida et al (2019), who analysed the same dataset and found that early growth initiated in August/September in the region south of ∼60°S. However, the authors do not explicitly investigate growth in relation to the release of melt waters in the SSIZ, and appear to conclude that melting generally initiates growth through the release of iron trapped in sea ice, as well as the relief of light limitation.…”
Section: Relationship Between Melting and Growthsupporting
confidence: 89%
“…Since the floats are being advected and may sample high‐frequency events like synoptic storms, each float time series is smoothed by a 30‐day running mean to highlight variability at seasonal time scales (Uchida et al, 2019). The median float displacement over the course of a full bloom cycle from October to May was 150 km, or 19 km over a 30‐day period.…”
Section: Methodsmentioning
confidence: 99%
“…Essentially, either phytoplankton are distributed relatively evenly through the mixed layer (no DCM, higher mixed-layer attenuation), or are present in a narrow band of elevated concentration at the base of the mixed layer (typically co-located with the nutricline: Cullen, 2015) forming a DCM below a relatively oligotrophic mixed-layer. It is difficult to forecast which of these will occur without good knowledge of the factors involved (inter alia water column structure, nutrient supply/demand, incident irradiance, photoadaptive-capability of phytoplankton species present, loss terms including grazing and sinking; Parslow et al, 2001;Kemp et al, 2006;Cullen, 2015;Carranza et al, 2018;Uchida et al, 2019), but we hypothesize that satellite data may be able to tell us which of these situations has occurred after the event.…”
Section: Deep-chlorophyll Maximamentioning
confidence: 99%
“…In addition, mixed layers can contain vertical structure in optical properties (Carranza et al, 2018). To evaluate the utility of E DCM as an indicator of DCM, a comparison was made between E DCM and the amount of phytoplankton biomass in the DCM from three Southern Ocean Carbon and Climate Observations and Modeling (SOCOMM project; Riser et al, 2018;Uchida et al, 2019) profiling drifters between 2013 and 2018. Phytoplankton biomass in the DCM was proxied from these float measurements as the depth-integrated phytoplankton carbon biomass (C p ) minus the surface phytoplankton carbon biomass multiplied by the mixed layer depth, C p (surf), following Uchida et al (2019).…”
Section: Deep-chlorophyll Maximamentioning
confidence: 99%
See 1 more Smart Citation